Immunotropic effects of mesotherapy used for correction of age-related skin changes - L. P. Sizyakina (SPb RAACI, 2021)
Rapid progression of aesthetic medicine is a distinctive feature of present decade. In this area, leading position is taken by injection cosmetology, which is associated with an opportunity of pathogenetic approach to resolution of cosmetic problems primarily caused by skin aging. The most commonly used mesotherapy drugs, along with hyaluronic acid, are vitamins, amino acids, and microelements. Skin aging is associated with quantitative and functional changes in the local immune cell populations. In this case, it is rational to assume distinct effects of peptide complexes upon functional potential of immunocompetent cells. The aim of this study was to analyze time-dependent changes of some immune parameters after mesotherapy with a complex of hyaluronic acid and peptides. The observation group consisted of 26 women who received their course of mesotherapy for the first time. Objective instrumental evaluation of the effect with Aramo Smart Lite device showed that, after mesotherapy, the skin quality was significantly improving in comparison with pre-treatment conditions, due to decreased relief of skin creases and wrinkles, with a tendency for reduction of this effect six months later. When comparing the results of immunological testing in the patients after the course of treatment with the data before starting the therapy, we have found redistribution in the lymphoid cell populations, i.e., increased proportion of T-lymphocytes, decreased amounts of B cells, and CD16+ natural killers. Declined numbers of T-lymphocytes expressing early activation marker were associated with increased proportion of peripheral Treg lymphocytes. We have also detected activation of antibody production which manifested as increased levels of all major classes of serum immunoglobulins. Enhanced spontaneous oxidative activity of neutrophils was also noted. The results of immunological monitoring showed that, three months post-treatment, none of the quantitative and functional parameters of immunity was changed, as compared with the results obtained immediately after ending the mesotherapy. Six months later, however, all these indexes returned to their initial positions assessed before the cosmetic procedure. The changes in systemic immune response following mesotherapy with peptide complexes affect the mechanisms of both innate and acquired immunity, including differentiation of lymphocytes, their regulatory functions and activation potential, and provide modulation of effector reactions. Complete restoration of initial immune parameters is observed within six months.